Implementation of a single sign-on system between practice, research and learning systems - Purkayastha, Saptarshi; Gichoya, Judy W.; Addepally, Abhishek Siva (Applied Clinical Informatics, 2017)
Background: Multiple specialized electronic medical systems are utilized in the health enterprise. Each of these systems has their own user management, authentication and authorization process, which makes it a complex web for navigation and use without a coherent process workflow. Users often have to remember multiple passwords, login/logout between systems that disrupt their clinical workflow. Challenges exist in managing permissions for various cadres of health care providers. Objectives: This case report describes our experience of implementing a single sign-on system, used between an electronic medical records system and a learning management system at a large academic institution with an informatics department responsible for student education and a medical school affiliated with a hospital system caring for patients and conducting research.Methods: At our institution, we use OpenMRS for research registry tracking of interventional radiology patients as well as to provide access to medical records to students studying health informatics. To provide authentication across different users of the system with different permissions, we developed a Central Authentication Service (CAS) module for OpenMRS, released under the Mozilla Public License and deployed it for single sign-on across the academic enterprise. The module has been in implementation since August 2015 to present, and we assessed usability of the registry and education system before and after implementation of the CAS module. 54 students and 3 researchers were interviewed.Results: The module authenticates users with appropriate privileges in the medical records system, providing secure access with minimal disruption to their workflow. No passwords requests were sent and users reported ease of use, with streamlined workflow.Conclusions: The project demonstrates that enterprise-wide single sign-on systems should be used in healthcare to reduce complexity like “password hell”, improve usability and user navigation. We plan to extend this to work with other systems used in the health care enterprise.
Keywords: Integrated information systems; electronic health records; educational needs; single sign-on; Security Assertion Markup Language; SAML; Central Authentication System; CAS